RIPHAH MEDICAL, DENTAL & PHYSIOTHERAPY FACULTY EXPERIENCE WITH ONLINE EDUCATION – COVID-19 PANDEMIC - Rahim, Amena; Ali, Shazia; Ali, Shabana; Fayyaz, Humaira (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the overall impact of using e-learning resources by Riphah faculty members in terms of their satisfaction and its usefulness for student learning. Study Design: Cross-sectional study.Place and Duration of Study: Conducted in Islamic International Medical College from 24th June to 28th June 2020.Methodology: There were a total of 160 respondents of Riphah faculty of Medical College (n=100), Dental College (n=30) and Rehab Sciences (n=30).Results: 58.8% of the faculty agreed that online education is convenient for their working and the concept of online mode of teaching was acceptable to 65.6%. Faculty -development workshops were appreciated by 60%. 70% disagreed that face-face lectures can be replaced by online lectures. Regarding Perception of student online teaching and assessment 66.9% disagreed that they are attentive during the online lectures. As far as the preparedness towards online learning was concerned 33.8% agreed that preparation for online lectures requires a lot of effort. 52.5% agreed that learning of online technologies is difficult to learn. Major challenges faced were those of network issues 56.3% lack of computer skills 64.4%. According to Kirk Patricks’ evaluation level-1 regarding the reaction of faculty 96.3% were satisfied with the faculty development program.Conclusion: Reaction of the employees is recorded to identify aspects, which can be used to make improvements in the training programs. A very high percentage of faculty members were satisfied with the training activities and strengths and weaknesses were elaborated along with the factors, which promote and hinder the students learning activities.